Does emigration benefit the stayers? The EU enlargement as a natural experiment. Evidence from Lithuania - Benjamin Elsner (Fondazione Eni Enrico Mattei (FEEM), 2010)
The eastern enlargement of the European Union in 2004 triggered a large flow of migrant workers from the new member states to the UK and Ireland. This paper analyzes the impact of this migration wave on the real wages in the source countries. I consider the case of Lithuania, which had the highest share of emigrants relative to its workforce among all ten new member states. Using data from the Lithuanian Household Budget Survey and the Irish Census, I find that emigration had a significant positive effect on the wages of men who stayed in the country, but no such effect is visible for women. A percentage point increase in the emigration rate increases the real wage of men on average by 1%. Several robustness checks confirm this result.
Keywords: F22; J61; R23; 330; Emigration; Labor Mobility; EU Enlargement